2019
DOI: 10.3389/fnins.2019.00540
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Response After Ischemic Stroke: Targeting β2 and β1 Integrins

Abstract: Ischemic stroke is a leading cause of death and disability with limited therapeutic options. Resulting inflammatory mechanisms after reperfusion (removal of the thrombus) result in cytokine activation, calcium influx, and leukocytic infiltration to the area of ischemia. In particular, leukocytes migrate toward areas of inflammation by use of integrins, particularly integrins β 1 and β 2 . Integrins have been shown to be necessary for leukocyte adhesion and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 126 publications
(140 reference statements)
0
29
0
Order By: Relevance
“…Moreover, it has been shown that HBO treatment inhibits ischemia reperfusion-induced neutrophil adhesion to endothelium by blocking β 2 integrin polarization [23,24] and may also reduce leukocytes recruitment as it impaired adhesion molecule function by S-nitrosation [25]. Conversely, the role played by α 4 β 1 integrin in neutrophil-mediated adhesion to endothelium has been poorly investigated but an important role of α 4 β 1 in β 2 integrin-independent migration of neutrophils across heart endothelium has been demonstrated in vitro, suggesting a similar in vivo situation in neutrophil trafficking in reperfused myocardium [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that HBO treatment inhibits ischemia reperfusion-induced neutrophil adhesion to endothelium by blocking β 2 integrin polarization [23,24] and may also reduce leukocytes recruitment as it impaired adhesion molecule function by S-nitrosation [25]. Conversely, the role played by α 4 β 1 integrin in neutrophil-mediated adhesion to endothelium has been poorly investigated but an important role of α 4 β 1 in β 2 integrin-independent migration of neutrophils across heart endothelium has been demonstrated in vitro, suggesting a similar in vivo situation in neutrophil trafficking in reperfused myocardium [26].…”
Section: Introductionmentioning
confidence: 99%
“…[26]. The leukocytes were attracted to vascular endothelium and aggregated in ischemic area, thus activating the secondary in ammatory reaction downstream and forming a vicious circle [27,28]. At the same time, 2-4 hours after the early stage of cerebral ischemia, microglia were activated by in ammatory cytokines, which further aggravated brain injury [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibition of integrin α2β1 may be a potential therapy for ischemic stroke. The expression and the role of integrins α8β1, α9β1, and αvβ6 have not yet been elucidated following stroke ( 147 ). At present, it is unknown if integrins influence TNC expression.…”
Section: Contribution Of Gfs and Integrins To Regulating Tnc Expressimentioning
confidence: 99%
“…In contrast, b1 integrins form laminin-binding, collagen-binding (a2b1), RGD-binding (a8b1), or ECMsbinding (a9b1) heterodimers (147)(148)(149)(150). The b1 integrins are increased in cerebral blood vessels in ischemic cortex, and induce angiogenesis as well as leukocyte adhesion and migration following ischemic stroke (147,151). In addition, increased b1 integrins in neuronal cells were associated with neuronal adhesion, and neurite outreach and regeneration (151).…”
Section: Integrinsmentioning
confidence: 99%